The Role of Influencer Marketing and E-Word of Mouth on Raecca's Product Purchase Decisions - Mayla Azahra; Lis Tatin Hernidatiatin (International Journal Labs, 2026)
The development of digital marketing encourages companies to utilize Influencer Marketing and Electronic Word of Mouth (E-WOM) strategies to influence consumer purchasing decisions. This study aims to analyze the influence of Influencer Marketing and E-WOM on Raecca product purchase decisions. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to 143 respondents who were consumers of Raecca products and met the research criteria. Data analysis was performed using multiple linear regression with the help of SPSS software. The results of the study show that Influencer Marketing has a positive and significant effect on the purchase decision of Raecca products. Meanwhile, Electronic Word of Mouth (E-WOM) also has a positive effect on Purchase Decisions, even though the level of significance is at the tolerance limit. Simultaneously, Influencer Marketing and E-WOM have been proven to have a significant influence on Purchase Decisions. The value of the determination coefficient showed that both independent variables were able to explain most of the variation in the Purchase Decision, while the rest were influenced by other factors outside the research model. The findings of this study confirm the importance of the role of Influencer Marketing and E-WOM as digital marketing strategies in shaping consumer purchasing decisions. The results of the research are expected to make a theoretical contribution to the development of marketing science and become practical considerations for companies in designing more effective digital marketing strategies.